SiC MOSFET device parameter spread and ruggedness of parallel multichip structures - Castellazzi, Alberto; Fayyaz, Asad; Kraus, Rainer (Trans Tech Publications, 2018)
This paper presents a preliminary study of the impact of device electro-thermal parameter spread and temperature variation on the robustness of SiC MOSFET parallel multi-chip power switch architectures. Reference is made to 1200 V – 80 mΩ rated commercial devices. Some major parameters are identified and selected, presenting experimental evidence of their impact during transient overload events. An advanced physics-based simulation model is then employed to extend the analysis to a more comprehensive set of parameters and operational conditions.